PENGARUH PEMBERIAN PUPUK NPK PADA MEDIA TANAM YANG BERBEDA TERHADAP PERTUMBUHAN TANAMAN KAMBOJA JEPANG (Adenium sp.) - Mita, Nastra; Silvina, Fetmi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Japanese cambodia(Adenium sp.) is one of the horticultural commodities of ornamental plant species whose beauty lies in the flowers, roots, and stems in the form of humps. The purpose of this study was to determine the best dose of NPK fertilizer and the composition of the appropriate growing media for the growth of Japanese frangipani (Adenium sp.) plants. This research was carried out in the experimental garden of the Faculty of Agriculture, Riau University, Bina Widya Campus Km 12.5, Simpang Baru Village, Tampan Pekanbaru District for seven months, from February-August 2019. The frangipani plant seeds used were ±2 months old with NPK pearl fertilizer (16:16:16). The study was conducted in a 4x3 factorial experiment using a randomized block design (RAK) which consisted of 2 factors, so there were 12 treatment combinations. Factor I (giving planting media) consisted of four levels and Factor II (giving compound NPK fertilizer) consisted of three level. The results showed that the use of Inceptisol 100% growing media gave a better impact on the increase in the number of leaves (strands), hump diameter (mm) and the number of flowers (buds), while the planting medium with husk charcoal mixture showed the fastest first flower. Dosage of 15g NPK fertilizer per plant gave a better impact on leaf area (cm2), bulb diameter (mm), flower appearance (days), and number of flowers (buds). Keywords : Japanese cambodia, growth, growing media, fertilizer